Avaliação da aprendizagem no primeiro e segundo ciclos de formação: ruptura ou continuidade da avaliação tradicional - Melo, Maria Noraelena Rabelo (2006)
This work is concerned with school evaluation and specifically the organization of education in cycles, implanted by the State Secretariat for Basic Education of Ceará in 1998, as a mechanism to revert the problem of academic failure, school abandonment and distortion of age/grades, in an effort to solve the old and serious phenomenon of school failure. This form of reorganizing the education al system demands a distinct concept of evaluation from that of simple measure and its restricted use of decisions to fail or approve the student. It demands a proper logic of the system in grades. Thus, we tried to analyze the results, in the practical evaluation by the teacher, of the changes introduced in the system of learning evaluation developed in the first and second Formation Cycles in the State of Ceará. The theoretical foundation was based on studies carried out by authors dealing with school evaluation from a sociological vision. A methodological procedure of a qualitative nature was adopted through a case study at a selected school in Fortaleza. For the collection of data, a documentary analysis was used, as well as a direct observation and interviews with the principal, the pedagogical coordinator, the supervisor, four teachers of the observed groups and two coordinators from the State Secretariat of Education of Ceará - SEDUC. The results show that the conditions offered to the schools and to the teachers caused almost no alteration in the practical evaluation by the teachers. The preoccupation with grades demonstrates that the changes proposed by the official agency, are not occurring. Thus, the present evaluation is not correct, but selecting and rejecting the students